Ghoulfriends - the ghoul-it-yourself book - Daneshvari, Gitty (Little, Brown and Company, 2014)
"Fang out with your ghoulfriends and engross yourself in the student unlife at Monster High. Bring this ghoul-it-yourself journal to Study Howl, the Creepateria, and the Maul to bond with your beasties over Ghoulish LIterature, scary-cool poems, delightfully dead dances, spooktacular fashions, and much more! Plus, Rocehlle shares her scary favorite rules from her beloved Gargoyle Code of Ethics."--Page 4 of cover
Keywords: High schools / Juvenile fiction; Friendship / Juvenile fiction; Monsters / Juvenile fiction; Diaries / Juvenile literature; High schools / Fiction; Friendship / Fiction; Monsters / Fiction; Diaries; Friendship; High schools; Monsters; Fiction; Juvenile works; Kinderbuch